The Role Of Work Stress In Mediating The Effect Of Workload And Compensation On Job Satisfaction - Pratama, Fajar Adi; Solihin, Agung (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This study aims to determine the role of work stress in mediating the influence of workload and compensation on job satisfaction in employees of PT Jasindo Pratama. The research design used is a causal relationship with a quantitative approach, which aims to find a cause-and-effect relationship between the variables studied. The population in this study is 45 employees of PT Jasindo Pratama, which is also used as a research sample using a saturated sampling technique. The data analysis method used is Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Data processing involves validity and reliability tests, structural tests, and hypothesis tests. The results of the study show that workload has a positive and significant influence on work stress. Workload has no effect on job satisfaction. Compensation has no effect on work stress. Compensation has a positive and significant influence on job satisfaction. Work stress has no effect on job satisfaction. Work stress cannot mediate the effect of workload and compensation on job satisfaction. Thus, these findings highlight the importance of the role of work stress in increasing job satisfaction among PT Jasindo Pratana employees. Although work stress cannot mediate the effect of workload and compensation on job satisfaction in the context of this study, it does not reduce the need to pay attention to and manage these factors in the context of human resource management.